Road to surrender eaudiobook Three men and the countdown to the end of world war ii. - Thomas, Evan (Books on Tape, 2023)
A riveting, immersive account of the agonizing decision to use nuclear weapons against Japan—a crucial turning point in World War II and geopolitical history—with you-are-there immediacy by the New York Times bestselling author of Ike’s Bluff and Sea of Thunder . “As Christopher Nolan’s movie Oppenheimer shows, the shockwaves reverberate still. The veteran biographer Evan Thomas now enters the debate.”— The Wall Street Journal AN NPR BEST BOOK OF THE YEAR At 9:20 a.m. on the morning of May 30, General Groves receives a message to report to the office of the secretary of war “at once.” Stimson is waiting for him. He wants to know: has Groves selected the targets yet? So begins this suspenseful, impeccably researched history that draws on new access to diaries to tell the story of three men who were intimately involved with America’s decision to drop the atomic bomb—and Japan’s decision to surrender. They are Henry Stimson , the American Secretary of War, who oversaw J. Robert Oppenheimer under the Manhattan Project; Gen. Carl “Tooey” Spaatz , head of strategic bombing in the Pacific, who supervised the planes that dropped the bombs; and Japanese Foreign Minister Shigenori Togo , the only one in Emperor Hirohito’s Supreme War Council who believed even before the bombs were dropped that Japan should surrender.   Henry Stimson had served in the administrations of five presidents, but as Oppenheimer’s work progressed, he found himself tasked with the unimaginable decision of determining whether to deploy the bomb. The new president, Harry S. Truman, thus far a peripheral figure in the momentous decision, accepted Stimson’s recommendation to drop the bomb. Army Air Force Commander Gen. Spaatz ordered the planes to take off. Like Stimson, Spaatz agonized over the command even as he recognized it would end the war. After the bombs were dropped, Foreign Minister Togo was finally able to convince the emperor to surrender. To bring these critical events to vivid life, bestselling author Evan Thomas draws on the diaries of Stimson, Togo and Spaatz, contemplating the immense weight of their historic decision. In Road to Surrender, an immersive, surprising, moving account, Thomas lays out the behind-the-scenes thoughts, feelings, motivations, and decision-making of three people who changed history.